2010
DOI: 10.1016/j.paid.2009.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Negative mood regulation expectancies, frontal lobe related behaviors and alcohol use

Abstract: . (2010) "Negative mood regulation expectancies, frontal lobe related behaviors and alcohol use" Personality and individual differences, 48 (3), 332-337.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
7
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
5
7
1
1
Order By: Relevance
“…The NMR scale has good psychometric properties (Cohen, McChargue & Morrell, 2007;Hasking, Lyvers & Carlopio, 2011) and has demonstrated discriminant validity from the Beck Depression Inventory, the Internal External Locus of Control Scale, and the Social Desirability Scale . The NMR scale typically shows negative correlations with indices of anxiety and depression (Catanzaro & Greenwood, 1994;Kassel, Jackson & Unrod, 2000;Kirsch, Mearns & Catanzaro, 1990) and with the FrSBe (Lyvers et al, 2010) in line with theoretical expectations.…”
Section: Fagerström Test For Nicotine Dependence (Ftnd)supporting
confidence: 83%
See 2 more Smart Citations
“…The NMR scale has good psychometric properties (Cohen, McChargue & Morrell, 2007;Hasking, Lyvers & Carlopio, 2011) and has demonstrated discriminant validity from the Beck Depression Inventory, the Internal External Locus of Control Scale, and the Social Desirability Scale . The NMR scale typically shows negative correlations with indices of anxiety and depression (Catanzaro & Greenwood, 1994;Kassel, Jackson & Unrod, 2000;Kirsch, Mearns & Catanzaro, 1990) and with the FrSBe (Lyvers et al, 2010) in line with theoretical expectations.…”
Section: Fagerström Test For Nicotine Dependence (Ftnd)supporting
confidence: 83%
“…Performance on a well-known neuropsychological test of frontal lobe related executive function, as well as a psychophysiological index of attention related to prefrontal cortex function, were both found to be deficient in nicotine-deprived current smokers compared to never-smokers or smokers who had just smoked a cigarette (Lyvers, Maltzman & Miyata, 1994;Lyvers & Miyata, 1993). As the ability to regulate one's own negative mood states by non-pharmacological means appears to be dependent on frontal lobe functioning (Lyvers, Thorberg, Ellul, Turner & Bahr, 2010), disruption of frontal systems may underlie mood problems in chronic smokers.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Not only are students with psychological distress prone to consume alcohol as a means to cope with negative affect (Gonzalez, Collins, & Bradizza, 2009; Lyvers, Thorberg, Ellul, Turner, & Bahr, 2010), but recent research has shown PBS to be especially valuable in reducing alcohol abuse and dependence among students with high coping motives (Patrick et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Por el contrario, cuando las emociones negativas se niegan e inhiben se produce un incremento en la excitación de algunas estructuras cerebrales (amígdala, Ínsula) y una disminución de la sensación de bienestar (Kassel, Bornovalova y Mehta, 2007;Speranza et al, 2005). Una inadecuada regulación emocional predispone a las adiciones y facilita la utilización del consumo de sustancias como forma de manejo del malestar afectivo (Catanzaro y Laurent, 2004;Kassel y Unrod, 2000;Lyvers, Thorberg, Ellul, Turner y Bahr, 2010). Esta afectación que se manifiesta a nivel cerebral se ha observado en estudios de resonancia magnética funcional.…”
unclassified